ANALISIS DAMPAK PENERAPAN IJIN USAHA TOKO MODERN TERHADAP KEBERADAAN PASAR TRADISIONAL DI KABUPATEN SLEMAN - IRNI SEPTIANI; INSIATININGSIH INSIATININGSIH (MANAJEMEN DEWANTARA, 2019)
The growth of Modern Stores in Indonesia is very rapid, experiencing growth from year to year, this condition is offset by demand from large communities and increasingly enjoys the convenience and comfort of shopping in modern stores. However, Sleman Regency D.I. Yogyakarta provides a number of rules as outlined in Regional Regulation No. 18 of 2012 concerning Licensing of Shopping Centers and Modern Stores, which it is hoped that this regulation will have a significant impact on equitable distribution between modern shops and traditional markets in Sleman Regency, YogyakartaReferring to the Regional Regulation, this research was carried out to see the impact of the application of the Modern Shop business permit to the existence of traditional markets in Sleman Regency D.I. Yogyakarta. In this study 200 samples were taken by distributing 250 questionnaires with a distribution of 125 questionnaires to managers and modern shop owners and 125 questionnaires to traditional shop owners in the traditional market of Sleman Regency D.I. Yogyakarta, which finally received 200 questionnaires. The method used for sampling is a non probability sampling method that is sampling by specifying specific criteria on respondents. Data collection techniques using questionnaires that have been tested for validity and reliability. Data analysis techniques using multiple linear regression analysis and data processed with SPSS software. The variables used in this study are 4 independent variables namely Business Location Aspects, Social Aspects, Partnership Aspects with MSMEs and Use of Local Workers Aspects, and 1 dependent variable namely the Existence of Traditional Markets. From the results of the research analysis it was concluded that the business location aspect variable (X1) had no impact on the existence of traditional markets with negative B1 (- 0.799) and t count was smaller than t table, Variable Social Aspects (X2) had no impact on the existence of Traditional Markets with B2 negative (-1,334) and t count smaller than t table, Variable Aspects of Partnership with MSME (X3) have an impact on the existence of Traditional Markets with positive B3 (9,153) and t count is greater than t table, Variable Aspects of Use of Power Local Work (X4) has an impact on the existence of Traditional Markets with positive B4 (1,646) and t count is greater than t table, and the four Independent Variables together have an impact on the dependent variable The existence of Traditional Market Sleman DIY Regency is allegedly also influenced by variables other variables not examined in this study.Keywords : modern shop, traditional market, Sleman Regency D.I. Yogyakarta, Existence of Traditional Markets